Chip Morphology In Ball Nose End Milling Process Of Nickel Based Alloy Material Under MQL Condition - Kasim, Mohd Shahir; Abdul Aziz, Mohd Sanusi; Mohd Shahrim, Mohammad Shah All-Hafiz; Wong, Pui Kei; Raja Abdullah, Raja Izamshah; W. Mohamad, W Noor Fatihah; Abdul Ghani, Jaharah; Haron, Che Hassan; Saedon, Juri (Springer, 2019)
This present paper deals with the chip segmentation in ball nose end milling process of Inconel 718 for turbine blades. It deals with characterizing the chip morphologies and microstructure investigations under minimum quantity lubrication (MQL) condition. In this study, the effects of cutting speed (Vc), radial depth of cut (WoC), and axial depth of cut (DoC) on chip segmentation are presented. The study proved that chip dimensional values were dominantly affected by the Vc, WoC, and DoC, while the frequency of dislodged chips was affected by notch wear. It was observed that the star anise-like chips formed are associated with the tool failure.